Severe anti‐thymocyte globulin‐induced cytokine release syndrome in a renal transplant patient. Issue 1 (13th January 2021) - Huh, J.; Baines, L.; Talbot, D.; MacFie, C.
Summary: Cytokine release syndrome is a systemic inflammatory response that can be triggered by a variety of factors such as infection or exposure to certain drugs, particularly novel T cell‐engaging immunotherapies. Severe cytokine release syndrome as a complication following treatment with anti‐thymocyte globulin, although recognised, is not well‐reported in the literature. We report the case of a 64‐year‐old man who developed catastrophic cytokine release syndrome after receiving anti‐thymocyte globulin during kidney transplantation. We highlight the importance of prompt recognition of severe cytokine release syndrome with strategies to aid survival in life‐threatening cases.